Between school factors and teacher factors: what inhibits Malaysian science teachers From using ICT? - Tunku Ahmad, Tunku Badariah (Universiti Malaya, 2014)
Despite the Malaysian government’s efforts to increase the use of ICT in school, teachers’ uptake of the technology remains slow and dismal. In this study, teachers’ perceptions of the barriers that inhibited their use of ICT in the science classroom were explored. One hundred and fifty-one (N = 151) science teachers from selected secondary schools in Kuala Lumpur and Selangor took part in the survey. Teachers’ perceptions of the barriers were captured using a self-developed questionnaire consisting of 27 Likert-type items. The questionnaires were administered with the help of school principals. Principal components analysis (PCA) with Promax rotation extracted four underlying dimensions of barriers to ICT use, namely teachers’ self-handicapping thoughts, school support, attitude toward ICT use, and negative beliefs about ICT use. Three of these factors were teacher related. Self-handicapping thoughts emerged as the largest inhibitor, explaining about 38.2% of teachers’ lack of ICT utilization in the science classroom. The results corroborated previous findings that teacher factors tend to outweigh school factors in hampering teachers’ uptake of technology.